(untitled) (Global Journal of Medical Research, 2024)
Background Investment in malaria control has dramatically reduced transmission An estimated 663 million cases have been averted worldwide between 2000 and 2015 with 68 attributed to insecticide-treated nets In recent years prevention in Eritrea has primarily relied on two main methods of intervention mass distribution of Long-Lasting Insecticide Nets LLINs and Indoor Residual Spraying IRS in specific areas prone to epidemics These are complemented by other supporting strategies like larval source management LSM While LLINs remain the primary prevention strategy in the study area the durability of nets distributed at different times has not been comprehensively assessed for their impact on 1 survival rate 2 fabric integrity and 3 insecticidal activity So this study was designed to address whether the nets distributed have been durable for three years under operational conditions